2000
DOI: 10.1097/00042560-200010010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Maternal Virus Load With Zidovudine, Didanosine, and Indinavir Combination Therapy Prevents Mother-to-Fetus HIV Transmission in Macaques

Abstract: Recently, we developed a maternal-fetal macaque model using a highly pathogenic HIV-2 strain, HIV-2287, to study the time course of HIV transmission in utero. Most pregnant macaques (Macaca nemestrina) infected with HIV-2287 (10-103 infective doses) transmitted HIV to their fetuses, as verified by positive identification of virus-infected mononuclear cells and free viral RNA in fetal blood. To determine whether an antiretroviral drug combination therapy composed of two dideoxynucleosides, azidothymidine (15 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…48 The HIV-2 287 nonhuman primate model of human HIV infection was proved valuable for the study of the events leading to lentivirus-induced immunodeficiency during an abbreviated time course. [18][19][20][21][22][23] We report consistent virus isolation from PBMCs by day 4 postinfection ( Table 1) and peak virus levels between days 10 and 14. We also found that cell-associated virus loads peaked in the ileum (Table 2 and Fig.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…48 The HIV-2 287 nonhuman primate model of human HIV infection was proved valuable for the study of the events leading to lentivirus-induced immunodeficiency during an abbreviated time course. [18][19][20][21][22][23] We report consistent virus isolation from PBMCs by day 4 postinfection ( Table 1) and peak virus levels between days 10 and 14. We also found that cell-associated virus loads peaked in the ileum (Table 2 and Fig.…”
Section: Discussionsupporting
confidence: 60%
“…[30][31][32][33][34][35] To more closely examine acute intestinal response to a highly pathogenic virus, we now report on a series of macaques infected by HIV-2 287 . [18][19][20][21][22][23] We found a clear correlation between local CD4 1 cell depletion and a drop in local antibody production. Moreover, the intestinal events in the intravenously infected macaques preceded CD4 1 cell depletion in the peripheral circulation by several days.…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations